Odd Harmonious Labeling of Subdivided Shell Graphs - Jeyanthi, P; Philo, S (International Journal of Computer Sciences and Engineering, 2025)
A graph G(p, q) is said to be odd harmonious if there exists an injection f: V(G) → {0, 1, 2, …, 2q-1} such that the induced function f*:E(G)→{1,3,...,2q−1} defined by f * (uv) = f(u) + f(v) is a bijection. In this paper we prove that the subdivided shell graph, disjoint union of two subdivided shell graph, subdivided shell flower graph and subdivided uniform shell bow graph are odd harmonious.